Credit risk management and its effect on the profitability of service sector listed on Bursa Malaysia / Nor Idayu Zainal Abiddin - Zainal Abiddin, Nor Idayu (2013)
This study attempts to reveal the relationship between credit risk management and its effect on the profitability of some selected firms in service sector listed on Bursa Malaysia. A panel data from sixty selected firms from service sector covering the three year period from 2010, 2011 and 2012 was analyzed within the fixed effects framework. This data was gathered from annual report of each company, and used the financial statements of each firms from the period of 2010 to 2012 (three years) for data analysis. The panel regression model was employed for the estimation. In the model, definition of Return on Equity (ROE) was used as profitability indicator while Non-Performing Loans Ratio (NLPR), pre provision profit ratio (PPPR) and Net Charge Off Ratio (NCOR) as credit risk management indicators. From the results, it shows that credit risk (non performing loan rate, net charge off rate, and the pre provision profit as a percentage of net total loans and advances) has a positive and significant relationship with firm profitability for each year. This indicates that firm in services sector enjoy high profitability in spite of high credit risk, contrary to the normal view held in previous studies that credit risk indicators are negatively related to profitability